Aquatic ecotoxicological models and their applicability in Arctic regions. Issue 1 (15th July 2017) - Fahd, Faisal; Khan, Faisal; Veitch, Brian; Yang, Ming
Abstract: Dose-response modeling is one of the most important steps of ecological risk assessment. It requires concentration-effects relationships for the species under consideration. There are very limited studies and experimental data available for the Arctic aquatic species. Lack of toxicity data hinders obtaining dose-response relationships for lethal (LC50 values), sub-lethal and carcinogenic effects. Gaps in toxicity data could be filled using a variety of in-silico ecotoxicological methods. This paper reviews the suitability of such methods for the Arctic scenario. Mechanistic approaches like toxicokinetic and toxicodynamic analysis are found to be better suited for interspecies extrapolation than statistical methods, such as Quantitative Structure-Activity Relationships/Quantitative Structure Activity-Activity Relationship, ICE, and other empirical models, such as Haber's law and Ostwald's equation. A novel approach is proposed where the effects of the toxicant exposure are quantified based on the probability of cellular damage and metabolites interactions. This approach recommends modeling cellular damage using a toxicodynamic model and physiology or metabolites interactions using a toxicokinetic model. Together, these models provide more reliable estimates of toxicity in the Arctic aquatic species, which will assist in conducting ecological risk assessment of Arctic environment. Highlights: Toxicokinetic (TK) and toxicodynamic (TD) models are better suited for Arctic aquatic environment. Limited discussion of the TD processes of cellular damage and recovery in aquatic animals Quantifiable linking of metabolite activity to cellular damage and recovery is proposed an approach.